Attitude and its relationship toward information and communication technology competency among vocational engineering students - Rinaldi, Rinaldi; Sari, Putri Gemala; Hamzah, Mohd Isa; Alimin, Masnaini (Universitas Negeri Padang, 2025)
There are gaps between vocational engineering curricula and industry competency needs, especially in information and communication technology (ICT) competency. However, limited studies have been conducted on factors affecting ICT competency among vocational engineering students, particularly attitudes toward ICT utilization. Thus, this study aims to determine the attitude and the relationship toward ICT competency among vocational engineering students based on the Unified Theory of Acceptance and Use of Technology II (UTAUT II). It was conducted in Higher Education Institutions in West Sumatera, Indonesia. It was a survey study with a quantitative method that used one set of questionnaires to collect data. Respondents are 805, covering first-year and last-year students enrolled in those institutions by purposive sampling. Data were analyzed descriptively for mean and standard deviation, and inferentially by employing Pearson Correlation. Findings showed that the ICT competency among vocational engineering students was lower than their attitude toward ICT utilization. A high attitude only is not enough to support the competency. Thus, this study can be used as a guide by the relevant authorities such as the Ministry of Education Affairs to take action to enhance the ICT competency among vocational engineering students from other aspects.